2023
DOI: 10.1136/gpsych-2022-100942
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review update on somatic symptom disorder that includes additional Chinese data

Heng Wu,
Ayinuer Manglike,
Yixiao Chen
et al.

Abstract: Somatic symptom disorder (SSD) is a new diagnosis introduced into the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5), which is expected to solve the diagnostic difficulties of patients with medically unexplained symptoms.Based on the previous work, this review aims to comprehensively synthesise updated evidence related to SSD from recent years in English publications and, more extensively, from data published in Chinese language journals.The scoping review update was based on an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…However, rigorous prevalence and diagnostic accuracy studies for SSD in primary care are still lacking. Recent scoping reviews ( 6 , 13 ) found that available prevalence estimates for SSD in primary care or the general population are based on proxy diagnoses based on self-report questionnaires. Other studies [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, rigorous prevalence and diagnostic accuracy studies for SSD in primary care are still lacking. Recent scoping reviews ( 6 , 13 ) found that available prevalence estimates for SSD in primary care or the general population are based on proxy diagnoses based on self-report questionnaires. Other studies [e.g.…”
Section: Discussionmentioning
confidence: 99%